1978
DOI: 10.1098/rspa.1978.0118
|View full text |Cite
|
Sign up to set email alerts
|

The Eckhaus and Benjamin-Feir resonance mechanisms

Abstract: A unified treatment is given of the Eckhaus mechanism of stability or instability of two-dimensional flows, which are periodic in one spatial dimension, and the Benjamin—Feir instability mechanism of the two-dimensional Stokes water wave. The method of the amplitude equation is used, following the lead of Newell in a related context. This method easily allows the analysis of the so-called side-band perturbations, which are a crucial feature of the Eckhaus and Benjamin—Feir resonance mechanisms. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(57 citation statements)
references
References 19 publications
3
54
0
Order By: Relevance
“…Our results for scalar equations extend those in [1,8,24], In [6] the stability of traveling wave solutions with respect to long-wavelength perturbations, that is small k , is discussed. In fact, however, caution must be exercised in extrapolating the result for stability to LW perturbations to larger values of k .…”
supporting
confidence: 52%
“…Our results for scalar equations extend those in [1,8,24], In [6] the stability of traveling wave solutions with respect to long-wavelength perturbations, that is small k , is discussed. In fact, however, caution must be exercised in extrapolating the result for stability to LW perturbations to larger values of k .…”
supporting
confidence: 52%
“…This can be seen from (9). In the limit of large amplitudes the diffusion coefficient becomes negative in the band center if c r d r + c i d i > 0 which is the condition for BenjaminFeir instability of the unforced waves [32]. This implies that either the parametrically forced waves become unstable at all wave numbers or the stable band has split into subbands.…”
Section: Discussionmentioning
confidence: 99%
“…The eventual instability is of the type discovered first by Benjamin and Feir in the frame of water waves [16]. It has been shown that this kind of instability involves the nonlinear interaction of two modulation terms with conjugated phases with the square A 2 of the constant solution [17]. Thus we write u as:…”
Section: Different Regimes For the Cgl Equation 321 The Stationary mentioning
confidence: 99%